PENDOPO PADEPOKAN TJIPTA BOEDAJA: REPRESENTASI ESTETIKA NUSANTARA DAN RUANG KOLEKTIF DALAM PELESTARIAN SENI TRADISIONAL: PENDOPO PADEPOKAN TJIPTA BOEDAJA: REPRESENTATION OF ARCHIPELAGO AESTHETICS AND COLLECTIVE SPACE IN TRADITIONAL ART PRESERVATION - Elianna Gerda Pertiwi; Sunarmi; Sarwanto (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
Padepokan Tjipta Boedaja in Tutup Ngisor Village, Magelang, is a traditional arts centre that has been running since 1937. As a collective space, the pavilion is a place for art preservation, social cohesion, and expression of cultural values. This research explores the aesthetic and social meanings of the pendopo using Y.B. Mangunwijaya's aesthetic theory. Through a qualitative approach and descriptive-analytical method, this research reveals the design elements of the pendopo that reflect the Nusantara philosophy, such as Gupala, Dewi Saraswati, and Yaksa Kala Liman ornaments, as well as the social function of the pendopo as an open and inclusive space. The results show that pendopo not only functions as a physical space, but also as a symbolic medium that strengthens cultural identity, supports art preservation, and builds community solidarity. This study provides a new perspective in understanding spatial design as an integral part of cultural preservation and social life.